2006
DOI: 10.1111/j.1399-3054.2006.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Stresses applied for the re‐programming of plant microspores towards in vitro embryogenesis

Abstract: Microspore embryogenesis is the most commonly used method to produce doubled haploids. It is based on the ability of a single haploid cell, the microspore, to de‐differentiate and regenerate into a whole plant after being exposed to stresses, such as low or high temperatures, carbon starvation and colchicine. Some stresses such as temperature treatments and carbon starvation have been used with success in many plant species, whereas others such as colchicine had limited application in a few species. Reports on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(134 citation statements)
references
References 137 publications
(154 reference statements)
2
123
0
9
Order By: Relevance
“…The result of the present study showed that cold stress could be effective for the improvement of indica rice anther culture. Different reasons have been suggested for the positive effect of cold pretreatment (Shahvali-Kohshour et al 2013;Shariatpanahi et al 2006). Cold pretreatment protects microspore from toxic compounds released in decaying anthers because it slows down degradation processes in the anther tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The result of the present study showed that cold stress could be effective for the improvement of indica rice anther culture. Different reasons have been suggested for the positive effect of cold pretreatment (Shahvali-Kohshour et al 2013;Shariatpanahi et al 2006). Cold pretreatment protects microspore from toxic compounds released in decaying anthers because it slows down degradation processes in the anther tissues.…”
Section: Discussionmentioning
confidence: 99%
“…which can be carried out by various pretreatments, such as heat, cold, starvation and chemical agents (reviewed by Zoriniants et al 2005 andShariatpanahi et al 2006). In the case of maize microspore and anther culture, tassels are usually pretreated by cold, placing the tassels at around 7 °C in the dark for 7-21 days (Gaillard et al 1991;Barnabás 2003).…”
mentioning
confidence: 99%
“…Among these treatments, chilling, high temperatures, high humidity, water stress, anaerobic treatment, centrifugation, sucrose and nitrogen starvation, addition of ethanol or a microtubuledisrupting agent, g-irradiation treatment, electrostimulation, culturing at a high pH, heavy metal treatment, etc., have been used in anther and microspore cultures. Shariatpanahi et al (2006) classified these treatments into the following three categories: widely used, neglected, and novel methods. Stress seems to act in different ways, by altering the polarity of the division at the first haploid mitosis, being involved in the reorganization of the cytoskeleton (Nitsch & Norreel 1973;Reynolds 1997), delaying and modifying pollen mitosis (two equal-sized vegetative-type nuclei instead of one The values within each column followed by different letters are significantly different at p # 0.05 (Games-Howell's test was used for undeveloped, swollen anthers and anthers with embryoids or embryogenic calli; Tukey's test was used for anthers with calli).…”
Section: Resultsmentioning
confidence: 99%